An Analysis of Cellular Communication Network Factor Proteins as Candidate Mediators of Postpartum Psychosis Risk - Davies, William (Frontiers in Psychiatry, 2019)
Postpartum (or puerperal) psychosis (PP) is a severe psychiatric condition associated with hallucinations, delusions, cognitive disorganisation and mood problems, which affects approximately 1-2 out of every 1000 new mothers shortly after childbirth. Whilst the risk factors for, and co-morbidities of, PP are relatively well-defined, currently the pathophysiology underlying the disorder is very poorly-specified. Here, I argue, on the basis of multiple lines of new evidence, that altered expression of the Cellular Communication Network (CCN) factor proteins (and of the heterodimerising CCN2 and CCN3 proteins in particular), may be associated with, and possibly causal for, increased PP risk. Future preclinical and clinical studies should aim to test this hypothesis as empirical support for it would provide much-needed clues regarding the biological substrates of PP, and could point to predictive biomarkers for the condition.